Cho hàm số f( x ) = 2/( x - 1)( x - 2). Tính lim x đến 2^ + f( x ) và lim x đến 2^ - f( x ).
Cho hàm số f(x)=2(x−1)(x−2).
Tính lim và \mathop {\lim }\limits_{x \to {2^ - }} f\left( x \right).
Cho hàm số f(x)=2(x−1)(x−2).
Tính lim và \mathop {\lim }\limits_{x \to {2^ - }} f\left( x \right).
Lời giải:
Ta có: f\left( x \right) = \frac{2}{{\left( {x - 1} \right)\left( {x - 2} \right)}} = \frac{2}{{x - 1}} \cdot \frac{1}{{x - 2}}
+) \mathop {\lim }\limits_{x \to {2^ + }} \frac{2}{{x - 1}} = \frac{2}{{2 - 1}} = 2 > 0 và \mathop {\lim }\limits_{x \to {2^ + }} \frac{1}{{x - 2}} = + \infty (do x – 2 > 0 khi x > 2).
Áp dụng quy tắc tìm giới hạn của tích, ta được \mathop {\lim }\limits_{x \to {2^ + }} f\left( x \right) = \mathop {\lim }\limits_{x \to {2^ + }} \frac{2}{{\left( {x - 1} \right)\left( {x - 2} \right)}} = + \infty .
+) \mathop {\lim }\limits_{x \to {2^ - }} \frac{2}{{x - 1}} = \frac{2}{{2 - 1}} = 2 > 0 và \mathop {\lim }\limits_{x \to {2^ - }} \frac{1}{{x - 2}} = - \infty (do x – 2 < 0 khi x < 2).
Áp dụng quy tắc tìm giới hạn của tích, ta được \mathop {\lim }\limits_{x \to {2^ - }} f\left( x \right) = \mathop {\lim }\limits_{x \to {2^ - }} \frac{2}{{\left( {x - 1} \right)\left( {x - 2} \right)}} = - \infty .